QOL-51. LISTENING BEFORE WE SPEAK: A PATIENT-CENTERED APPROACH TO DEVELOPING RESOURCES FOR PEDIATRIC BRAIN TUMOR SURVIVORS AND THEIR FAMILIES. (4th December 2020) - Riley, Kathy
Abstract: In the United States, more than 28, 000 children and teenagers live with the diagnosis of a primary brain tumor (Porter, McCarthy, Freels, Kim, & Davis, 2010). In 2017, an estimated 4, 820 new cases of childhood primary brain and other central nervous system tumors were expected to be diagnosed in children ages 0 – 19 in the United States (Central Brain Tumor Registry of the United States, 2017). Survivors suffer from lifelong side effects caused by their illness or by various treatments. Commonly identified late effects of treatment include a decline in intellectual functioning and processing speed, performance IQ deficits, memory deficits, psychological difficulties, deficits in adaptive functioning (daily life skills), and an overall decrease in health-related quality of life (Castellino, Ullrich, Whelen, & Lange, 2014). To address the ongoing challenges these survivors and their families face, the Pediatric Brain Tumor Foundation (PBTF) met extensively with working groups comprised of survivors and caregivers to develop the outline for a comprehensive Survivorship Resource Guidebook. In 2019, the PBTF published the guidebook which categorizes survivor and caregiver needs into three primary areas: physical and mental health, quality of life, and working the system. Expert authors included survivors and caregivers themselves in addition to medical and mental health professionals. Key outcomes discovered during the creation and production of this resource highlight how caregivers, survivors and professionals can collaborate to provide needed information and practical help to one segment of the pediatric cancer population who experience profound morbidities as a result of their diagnosis and treatment.